Pengaruh Harga, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Rizqy Bakery Bangkalan (Studi Pada Konsumen Rizqy Bakery Bangkalan) - Alisiyah, Hoomzah Nur; Kurriwati, Nirma (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The purpose of this study was to determine the effect of price, product quality and brand image on purchasing decisions of Rizky Bakery Bangkalan, either partially or simultaneously on purchasing decisions. This research uses quantitative methods. The data analysis technique used is multiple linear regression analysis. The sampling technique used the non-probability sampling technique with the sampling method using the purposive sampling method which obtained as many as 80 respondents. The population used in this study are consumers who have purchased Rizky Bakery Bangkalan products. The results of this study indicate that price, product quality and brand image have a partial effect on purchasing decisions. Price, product quality and brand image have a simultaneous influence on purchasing decisions.